Screening of chemokine receptor CCR4 antagonists by capillary zone electrophoresis - Zhe Sun; Lin-Jie Tian; Qian Lin; Xiao-Mei Ling; Jun-Hai Xiao; Ying Wang (Elsevier, 2011)
CC chemokine receptor 4 (CCR4) is a kind of G-protein-coupled receptor, which plays a pivotal role in allergic inflammation. The interaction between 2-(2-(4-chloro-phenyl)-5-{[(naphthalen-1-ylmethyl)-carbamoyl]-methyl}-4-oxo-thiazolidin-3-yl)-N-(3-morpholin-4-yl-propyl)-acetamide (S009) and the N-terminal extracellular tail (ML40) of CCR4 has been validated to be high affinity by capillary zone electrophoresis (CZE). The S009 is a known CCR4 antagonist. Now, a series of new thiourea derivatives have been synthesized. Compared with positive control S009, they were screened using ML40 as target by CZE to find some new drugs for allergic inflammation diseases. The synthesized compounds XJH-5, XJH-4, XJH-17 and XJH-1 displayed the interaction with ML40, but XJH-9, XJH-10, XJH-11, XJH-12, XJH-13, XJH-14, XJH-3, XJH-8, XJH-6, XJH-7, XJH-15, XJH-16 and XJH-2 did not bind to ML40. Both qualification and quantification characterizations of the binding were determined. The affinity of the four compounds was valued by the binding constant, which was similar with the results of chemotactic experiments. The established CEZ method is capable of sensitive and fast screening for a series of lactam analogs in the drug discovery for allergic inflammation diseases. Keywords: Capillary zone electrophoresis, CCR4 antagonist, 2-(2-(4-chloro-phenyl)-5-{[(naphthalen-1-ylmethyl)-carbamoyl]-methyl}-4-oxo-thiazolidin-3-yl)-N-(3-morpholin-4-yl-propyl)-acetamide, Interactions, Structural modification